Théorie du changement - Esplanade Québec (Esplanade, 2021)
Une théorie du changement est un outil qui vous aide à décrire les changements que vous voulez voir se produire et la manière dont vous comptez y parvenir. Plus spécifiquement, elle vous aide à décrire le problème que vous essayez de résoudre, les changements que vous voulez opérer (vos résultats) et ce que vous allez mettre en place pour pouvoir y arriver (activités). Elle est une représentation dynamique et une illustration du comment et du pourquoi il est envisagé que le changement désiré s’opère dans un contexte particulier.
Keywords: Canevas; Libre accès; Mesure d'impact; Montréal; Optimisation; Outils; Planification; Québec; Théorie du changement

Boîte à outils - Maison de l'innovation sociale - MIS
Dans le cadre des parcours d’accompagnement et des services offerts par la MIS, nous proposons divers outils afin de soutenir les porteurs et porteuses de projets à fort impact social et environnemental.
Keywords: Impact environnemental; Impact social; Innovation sociale; Libre accès; Mobilisation; Montréal; Outils; Planification; Québec; Soutien

Solving the Puzzle of Collaborative Governance - Weaver, Liz (Tamarack Institute, 2021)
There is a substantive amount of literature about collaboration and collaborative work but relatively little that identifies the nuts and bolts of collaborative governance including process, structure, accountability, engagement, and effectiveness. This article is for changemakers encountering challenges with collaborative governance within their work.
Aussi en français https://www.tamarackcommunity.ca/library/solving-the-puzzle-of-collaborative-governance
Keywords: Canada; Libre accès

Social Innovation For Health Research: Development of the SIFHR Checklist - Kpokiri, Eneyi E.; Chen, Elizabeth; Li, Jingjing; Payne, Sarah; Shrestha, Priyanka; Afsana, Kaosar; Amazigo, Uche; Awor, Phyllis; de Lavison, Jean-Francois; Khan, Saqif; Mier-Alpaño, Jana; Ong, Alberto; et al. (PLOS Medicine, 2021)
Background Social innovations in health are inclusive solutions to address the healthcare delivery gap that meet the needs of end users through a multi-stakeholder, community-engaged process. While social innovations for health have shown promise in closing the healthcare delivery gap, more research is needed to evaluate, scale up, and sustain social innovation. Research checklists can standardize and improve reporting of research findings, promote transparency, and increase replicability of study results and findings. Methods and findings The research checklist was developed through a 3-step community-engaged process, including a global open call for ideas, a scoping review, and a 3-round modified Delphi process. The call for entries solicited checklists and related items and was open between November 27, 2019 and February 1, 2020. In addition to the open call submissions and scoping review findings, a 17-item Social Innovation For Health Research (SIFHR) Checklist was developed based on the Template for Intervention Description and Replication (TIDieR) Checklist. The checklist was then refined during 3 rounds of Delphi surveys conducted between May and June 2020. The resulting checklist will facilitate more complete and transparent reporting, increase end-user engagement, and help assess social innovation projects. A limitation of the open call was requiring internet access, which likely discouraged participation of some subgroups. Conclusions The SIFHR Checklist will strengthen the reporting of social innovation for health research studies. More research is needed on social innovation for health.
Table 2 - intéressante à l’étape d’organiser son projet
Keywords: Innovation inclusive; Innovation sociale; Libre accès; Santé